2011
DOI: 10.4049/jimmunol.1003236
|View full text |Cite
|
Sign up to set email alerts
|

Polypyrimidine Tract-Binding Protein Is Critical for the Turnover and Subcellular Distribution of CD40 Ligand mRNA in CD4+ T Cells

Abstract: CD40 ligand (CD40L or CD154) is regulated at the posttranscriptional level by an activation-induced process that results in a highly stable transcript at extended times of T cell activation. Transcript stability is mediated by polypyrimidine tract-binding protein (PTB)-containing complexes (Complex I and II) that bind to three adjacent CU-rich sequences within the 3′ untranslated region (3′UTR). To assess the role of PTB in the expression and distribution of CD40L mRNA, PTB was targeted using shRNA in both pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…41 Similar studies have demonstrated PTBP1's ability to regulate subcellular distribution of STX1B, VAMP2, SV2A, KIF5 and CD40L mRNA. 29,42 To determine whether PTBP1 influenced MCL1 mRNA cellular distribution, we performed nucleo-cytoplasmic fractionation of both protein and RNA in siControl and siPTBP1 cells. Both protein lysates and RNA extracts from whole-cell, cytoplasmic and nuclear fractions were collected.…”
Section: Knockdown Of Ptbp1 Upregulates Mcl1 Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Similar studies have demonstrated PTBP1's ability to regulate subcellular distribution of STX1B, VAMP2, SV2A, KIF5 and CD40L mRNA. 29,42 To determine whether PTBP1 influenced MCL1 mRNA cellular distribution, we performed nucleo-cytoplasmic fractionation of both protein and RNA in siControl and siPTBP1 cells. Both protein lysates and RNA extracts from whole-cell, cytoplasmic and nuclear fractions were collected.…”
Section: Knockdown Of Ptbp1 Upregulates Mcl1 Expressionmentioning
confidence: 99%
“…PTBP1 is a RNA binding protein that regulates RNA splicing, IRES (internal ribosome entry segment)-mediated translation initiation, 3′-end processing, mRNA turnover, localization, and transportation. 28 PTBP1 has been shown to be involved in distinct cellular processes including T-cell activation, 29 HCV replication and infection, 30 insulin secretion, 31 and apoptosis [32][33][34] through its post-transcriptional control of RNA. Recent studies have highlighted that PTBP1 expression is often dysregulated in human cancer, though its effect on malignancy appears to be cell-type dependent.…”
mentioning
confidence: 99%
“…There are other phosphorylation sites on PTB in addition to Ser16, and other posttranslational modifications are also likely present. Cytoplasmic relocalization is presumably required for PTB’s known cytoplasmic functions such as the control of mRNA localization, translation, and mRNA stability (Hamilton et al, 2003; de Hoog et al, 2004; Fred et al, 2006; Lewis et al, 2008; Sawicka et al, 2008; Matus-Nicodemos et al, 2011). …”
Section: Ptb Interacting Proteinsmentioning
confidence: 99%
“…These proteins, including the SR proteins, many of the original hnRNP proteins (notably A1, H, L), the CELF, Nova, Rbfox, and Muscle blind families, and others, belong to a variety of structural families and have different RNA recognition properties and different patterns of expression in tissues (Graveley, 2000; Dreyfuss et al, 2002; Black, 2003; Chen and Manley, 2009; Kalsotra and Cooper, 2011). In addition to their nuclear role in RNA processing, these proteins, including PTB, also often affect cytoplasmic processes such as mRNA localization, translation or decay (Hellen et al, 1993; Cote et al, 1999; Kim et al, 2000; Tillmar and Welsh, 2002; Hamilton et al, 2003; de Hoog et al, 2004; Bushell et al, 2006; Fred et al, 2006; Sawicka et al, 2008; Babic et al, 2009; Besse et al, 2009; Kafasla et al, 2009; Cobbold et al, 2010; Matus-Nicodemos et al, 2011). Within the nucleus, these proteins affect large programs of alternative processing events (Ule et al, 2006; Boutz et al, 2007b; Kalsotra et al, 2008; Licatalosi et al, 2008; Xue et al, 2009; Yeo et al, 2009; Kalsotra and Cooper, 2011).…”
mentioning
confidence: 99%
“…PTBP1 is a multifunctional protein, with well‐described functions in splicing, translation, polyadenylation, and mRNA stability. In T cells, PTBP1 has been shown to bind to the 3′‐UTR of the CD40 ligand ( CD154 ) mRNA, stabilizing it during activation of T cells, which corresponds to the temporal expression of CD154 . In other cell types, PTBP1 was shown to bind to cis ‐elements in the pre‐mRNA and modulate PAS usage .…”
Section: Discussionmentioning
confidence: 99%